Damage evolution mechanism of loess slope under the combination of freeze-thaw cycles and earthquake. Issue 166 (March 2023) - Yuan, Ganglie; Wu, Zhijian; Che, Ailan; Zhou, Hanxu
Abstract: The Loess Plateau in China is composed of a large number of frozen soil with frequent earthquakes. Freeze-thaw cycles and earthquakes both lead to soil damage and strength degradation, resulting in a large number of landslides. However, the research on damage evolution mechanism of loess slope under the combination of freeze-thaw cycles and earthquake is weak. Considering the effect of freeze-thaw cycles and earthquake on loess slopes, a shaking-table test on slope models with and without freeze-thaw cycles was conducted and the slope damage was monitored in real time through electrical measurement. The results indicate that the loess damage caused by freeze-thaw cycles aggravated the response of slope during earthquake—"Freeze-thaw and earthquake mutual promotion effect". The damage factor increased slowly to 0.17 due to the moisture migration and pore connectivity during freeze-thaw cycles, and it increased rapidly to 0.69 due to continuous cracks expand during earthquake. Moreover, the cyclic migration of water to the slope surface caused by freeze-thaw cycles and vibration intensifies the damage along slope in the deep direction. Damage depth (30 cm) is greater than frozen depth (10 cm), increasing the risk of the deep loess landslide. Highlights: A shaking-table test on slope models with freeze-thaw cycles was conducted. Freeze-thaw and earthquake mutual promotion effect on slope damage is observed. Damage evolution mechanism of loess slope under the combination of FTCs and earthquake is clarified.